Cosmic ray source and solar energetic particles - Cassé, M.; Maslov, V.I. (Problems of Atomic Science and Technology, 2023)
The acceleration of particles to the high energy is one of the key issues of solar physics, cis-lunar irradiations, astrophysics, and astroparticle physics. With the development of space astronomy, people started to realize that plasma disturbances in solar flares, Earth’s magnetosphere, and interplanetary space can also produce a large population of non-thermal particles. Cosmic ray promotion i.e. selective energization of matter in the cosmos requires, as on earth, three distinct stages: ionization, injection and acceleration to high energy. Supernova remnants and stellar winds of massive stars grouped in associations appear to be excellent celestial accelerators or re-accelerators through the shock waves they induce in their superbubbles. The injection of ions seems devoted to stars, except the smaller ones. In cosmic several mechanisms lead charged particle acceleration. Electrons are accelerated in direction of Earth’s poles by long train of electric double layers of small amplitudes. Charged particles are accelerated by the pondermotive force of electromagnetic radiation. Also, in a nonequilibrium current plasma or a plasma with particle flows, a strong electric double layer can be formed, which accelerates charged particles to high energies. The reconnection of the magnetic field lines also leads to the acceleration of charged particles. Прискорення частинок до високої енергії є одним із ключових питань фізики Сонця, астрофізики та астрофізики частинок. З розвитком космічної астрономії люди почали усвідомлювати, що плазмові збурення сонячних спалахів, магнітосфери Землі та міжпланетного простору також можуть породжувати велику популяцію нетеплових частинок. Просування космічного випромінювання, тобто вибіркова активізація матерії в космосі, вимагає, як і на Землі, трьох різних етапів: іонізації, інжекції та прискорення до високої енергії. Залишки наднових і зоряні вітри масивних зірок, які згруповані в асоціації, виявляються чудовими небесними прискорювачами або повторними прискорювачами через ударні хвилі, які вони викликають у своїх супербульбашках. Інжекція іонів, здається, присвячена зіркам, за винятком малих. У космосі кілька механізмів призводять до прискорення заряджених частинок. Електрони прискорюються в напрямку полюсів Землі довгою серією подвійних електричних шарів малих амплітуд. Заряджені частинки прискорюються пондермоторною силою електромагнітного випромінювання. Крім того, у нерівноважній плазмі зі струмом або плазмі з потоками частинок може утворюватися сильний подвійний електричний шар, який прискорює заряджені частинки до високих енергій. Перез’єднання силових ліній магнітного поля також призводить до прискорення заряджених частинок.